2019
DOI: 10.1111/jbi.13617
|View full text |Cite
|
Sign up to set email alerts
|

Over the hills, but how far away? Estimates of mushroom geographic range extents

Abstract: Aim Geographic distributions of mushroom species remain poorly understood despite their importance for advancing our understanding of the habitat requirements, species interactions and ecosystem functions of this key group of organisms. Here, we estimate geographic range extents (maximum within‐species geographic distance) of genetically defined operational taxonomic units (OTUs). Location World‐wide, with emphasis on the American Pacific Northwest. Taxa Amanita, Agaricus, Cortinarius, Galerina, Hebeloma, Hydn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
5
2
Order By: Relevance
“…Additionally, the number of saprotrophic OTUs significantly changed with distance from the creek shore, with an uptick at an intermediate distance while there was no difference found in EM fungi. Interestingly, mycorrhizal fungi have been predicted to display more restricted ranges compared to saprotrophs [68], although global empirical data failed to recover this pattern [69]. This would lead to a prediction of edaphic factors affecting mycorrhizal fungi disproportionately, which is the opposite of what we found.…”
Section: Discussioncontrasting
confidence: 70%
“…Additionally, the number of saprotrophic OTUs significantly changed with distance from the creek shore, with an uptick at an intermediate distance while there was no difference found in EM fungi. Interestingly, mycorrhizal fungi have been predicted to display more restricted ranges compared to saprotrophs [68], although global empirical data failed to recover this pattern [69]. This would lead to a prediction of edaphic factors affecting mycorrhizal fungi disproportionately, which is the opposite of what we found.…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, large intercontinental distributions appear to be a trend in Arctic and alpine ectomycorrhizal genera and implies that species maintain large, intercontinental populations. This is in contrast with data from other habitats that show most ectomycorrhizal fungi have small geographic distributions (Bazzicalupo et al 2019) and that spore dispersal from basidiocarps appears limited (Fischer et al 2010). Although we do not have data to explain the large, intercontinental distributions found here for alpine species of Russula in the Rocky Mountains, we believe that one of the most parsimonious explanation is that Arctic and alpine fungi are following their primary host, dwarf and shrubby species of Salix.…”
Section: Phylogenetic Analysiscontrasting
confidence: 64%
“…Another study analyzed DNA from sporocarps and soil samples to determine that Russula was the fifth most species-rich genus in Svalbard (Geml et al 2012). They proposed that long-distance, transoceanic dispersal occurs in Arctic fungi, in contrast to the more limited dispersal of temperate Russula species (Bazzicalupo et al 2019). As molecular tools became easier to use and more reliable, researchers began to sort out and clarify certain groups of Russula.…”
Section: Russula In Arctic-alpine Habitats Of Europe Asia and Arctic Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned study demonstrated that most ECM fungi could only be distributed in regions with ECM plant taxa that are similar to those on Yakushima Island, implying that the distribution ranges of ECM fungi are restricted by host specificity rather than by climate preference and dispersal limitations. Since the global distribution of ECM fungi has been rarely investigated ( Sato et al, 2012 ; Tedersoo et al, 2014 ; García-Guzmán et al, 2017 ; Bazzicalupo et al, 2018 ), further studies are required to elucidate the influence of host specificity on the distribution ranges of ECM fungi.…”
Section: Introductionmentioning
confidence: 99%